CD44 and vimentin, markers involved with epithelial-mesenchymal transition: A proteomic analysis of sequential proteins extraction of triple-negative breast cancer cells after treatment with all-trans retinoic acid - Strouhalova, Dana; Macejova, Dana; Lastovickova, Marketa; Brtko, Julius; Bobalova, Janette (General physiology and biophysics, 2020)
This work aimed to provide, in one isolation and separation step, an overview of the content of proteins with different solubility after treatment with all-trans retinoic acid, which is considered to be an important therapeutic agent, predominantly in acute promyelocytic leukemia. Breast, ovarian, bladder, and skin cancers have been demonstrated to be suppressed by retinoic acid, as well. The bottom-up proteomic strategies were applied for the analysis of proteins extracted from triple-negative breast cancer MDA-MB-231 cells utilizing a commercially manufactured kit. The gel electrophoresis followed by MALDI-TOF MS analysis was used for protein determination. By employing PDQuest™ software, we identified several proteins affected by all-trans retinoic acid. Two proteins, vimentin and CD44, which are associated with the epithelial-mesenchymal transition, were selected for a detailed study. We have found that all-trans retinoic acid results in significantly reduced levels of vimentin and CD44 in both the cytoplasmic and membrane fractions. A significant effect was particularly evident in CD44, where protein level in the cytoplasmic fraction was almost completely suppressed.
Keywords: Proteomics; nádorové buněčné linie; triple-negativní karcinom prsu; Epithelial-Mesenchymal Transition; Hyaluronan Receptors; Cell Line, Tumor; Humans; Tretinoin; proteomika; lidé; Vimentin; tretinoin; epitelo-mezenchymální tranzice; antigeny CD44; vimentin; Triple Negative Breast Neoplasms